2017
DOI: 10.1371/journal.pone.0173439
|View full text |Cite
|
Sign up to set email alerts
|

Struggling toward reward: Recent experience of anhedonia interacts with motivation to predict reward pursuit in the face of a stressful manipulation

Abstract: Anhedonia, or the loss of interest and/or pleasure, is a core symptom of depression. Individuals experiencing anhedonia have difficulty motivating themselves to pursue rewarding stimuli, which can result in dysfunction. Action orientation is a motivational factor that might interact with anhedonia to potentially buffer against this dysfunction, as action-oriented individuals upregulate positive affect to quickly motivate themselves to complete goals in the face of stress. The Effort-Expenditure for Rewards Tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
(70 reference statements)
1
9
0
Order By: Relevance
“…“Loss of satisfaction” (“I am dissatisfied or bored with everything”; BDI-4) and “loss of interest in people” (BDI-12) were also identified as core symptoms in the depressive symptom–patient activation network. This finding supports previous studies, 34 , 35 which argue that the affective symptoms of depression such as anhedonia can thwart even small behavioral changes needed to manage chronic medical illnesses. Interestingly, previous studies have shown that these affective symptoms of depression appear to be particularly cardiotoxic.…”
Section: Discussionsupporting
confidence: 91%
“…“Loss of satisfaction” (“I am dissatisfied or bored with everything”; BDI-4) and “loss of interest in people” (BDI-12) were also identified as core symptoms in the depressive symptom–patient activation network. This finding supports previous studies, 34 , 35 which argue that the affective symptoms of depression such as anhedonia can thwart even small behavioral changes needed to manage chronic medical illnesses. Interestingly, previous studies have shown that these affective symptoms of depression appear to be particularly cardiotoxic.…”
Section: Discussionsupporting
confidence: 91%
“…For example a recent study in adults examining The Effort-Expenditure for Rewards Task (EEfRT) [52] has found that at low levels of anhedonia, action orientation (a motivation factor) was associated with effort for reward, but this relationship was not present at high levels of anhedonia. Thus, at low levels of anhedonia, action orientation acted as a buffer against stress, but at high levels, anhedonia debilitated action orientation so that it was no longer a promotive factor [53]*. In our recent study with adolescents at high risk of depression compared to controls we also measured effort but using button presses to win chocolate taste and avoid an unpleasant taste using this method we did not find behavioural differences in effort between groups.…”
Section: Anhedonia and Physical Effort In Adolescent Depressionmentioning
confidence: 84%
“…Recent changes in anhedonia that include loss of interest or pleasure may be specific to individuals avoiding positivity 4,12,13,70. Thus, avoidance of reward is a crucial candidate variable for future research that will unpack how and why individuals develop and maintain anhedonic symptoms.…”
Section: Moving Forward With Anhedonia Research: the Challenge Of Rewmentioning
confidence: 99%